Influence of difference deposition technique of Nickel on the FeCrAl Metallic Monolith - Darwin, Sebayang; P., Untoro; Y., Putrasari; Y.H., Soon; M., Hashim; M., Ghooma (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.